The role of pre-biopsy mpMRI in lymph node staging for prostate cancer. Issue 1 (February 2022) - Abou Heidar, Nassib; El-Doueihi, Robert; Merhe, Ali; Ramia, Paul; Bustros, Gerges; Yacoubian, Aline; Jaafar, Rola; Nasr, Rami
Introduction: Prostate cancer (PCa) staging is an integral part in the management of prostate cancer. The gold standard for diagnosing lymph node invasion is a surgical lymphadenectomy, with no superior imaging modality available at the clinician's disposal. Our aim in this study is to identify if a pre-biopsy multiparametric MRI (mpMRI) can provide enough information about pelvic lymph nodes in intermediate and high risk PCa patients, and whether it can substitute further cross sectional imaging (CSI) modalities of the abdomen and pelvis in these risk categories. Methods: Patients with intermediate and high risk prostate cancer were collected between January 2015 and June 2019, while excluding patients who did not undergo a pre-biopsy mpMRI or a CSI. Date regarding biopsy result, PSA, MRI results, CSI imaging results were collected. Using Statistical Package for the Social Sciences (SPSS) version 24.0, statistical analysis was conducted using the Cohen's Kappa agreement for comparison of mpMRI with CSI. McNemar's test and receiver operator curve (ROC) curve were used for comparison of sensitivity of both tests when comparing to the gold standard of lymphadenectomy. Results: A total of 143 patients fit the inclusion criteria. We further stratified our patients into according to PSA level and Gleason score. Overall, agreement between mpMRI and all CSI was 0.857. When stratifying patients based on Gleason score and PSA, the higher the grade or PSA, the higher agreement between mpMRI and CSI. The sensitivity of mpMRI (73.7%) is similar to CSI (68.4%). When comparing CSI sensitivity to that of mpMRI, no significant difference was present by utilizing the McNemar test and very similar receiver operating characteristic curve. Conclusion: A pre-biopsy mpMRI can potentially substitute further cross sectional imaging in our cohort of patients. However, larger prospective studies are needed to confirm our findings.